Receipt for gold dust despatched from Melbourne to London - Jones, Henry (1852)
Receipt for 120 oz of gold dust despatched from Melbourne to London on board the ship "Ballarat". Signed by Henry Jones, Master of the "Ballarat."
Manuscript reference no. : NLA MS 1318.
Positive and negative photocopies.
Location of original unknown.
Keywords: Ballarat (Ship).